FRI0107 Five successful pregnancies with antenatal anakinra exposure. (12th June 2018) - Smith, C.J.F.; Chambers, C.
Abstract : Background: Current recommendations are to discontinue the interleukin-1 (IL-1) inhibitor anakinra prior to pregnancy given lack of safety evidence. 1 A total of 39 previous exposed pregnancies have been documented in the literature, and two resulting cases of fetal renal agenesis have been described. 2, 3 Objectives: Our aim is to add to the limited existing data on IL-1 inhibitor use in pregnancy. Methods: Data were obtained from the Organisation of Teratology Information Specialists (OTIS) Autoimmune Disease in Pregnancy Project, a prospective cohort study of pregnancy outcomes in the U.S. and Canada. Eligible women enrolled prior to 19 weeks' gestation between 2004 and 2017. Women who consented to participate were interviewed two to three times during pregnancy with a standard questionnaire regarding medical history, exposures during pregnancy, and demographic characteristics. Outcomes were obtained by maternal interview and medical record abstraction. Results: Five pregnancies with anakinra exposure were identified, all resulting in full-term singleton live births, mean gestational age at delivery of 38.9 weeks, with no major or long-term infant complications. Three maternal subjects used anakinra for adult-onset Still's disease (AOSD) and two for juvenile idiopathic arthritis (JIA). One mother was diagnosed with AOSD during pregnancy, and anakinra was started at 20 weeks' gestation. All other subjects had a known diagnosis prior to pregnancy, and four subjects used the medication into the third trimester. All maternal subjects used 100 mg dosing of anakinra, four with daily use, one with weekly use. For all subjects who discontinued anakinra, some amount of steroid medication was necessary for treatment of disease flare. Two subjects developed oligohydramnios, one also with pregnancy-induced hypertension. Two women had caesarian sections, one medically-indicated and one scheduled. One infant had low birth weight, but follow-up records indicated normal adjusted weight at one year. Three women successfully breastfed their infants, at least two of whom continued anakinra while breastfeeding. Conclusions: Anakinra was used successfully in five full term pregnancies. Two subjects developed oligohydramnios, however. With the two previous reported cases of fetal renal agenesis, a process leading to low fluid levels, and the fact that maternal hyperthermia has been previously linked to fetal renal anomalies, 4 it is worth further exploring the potential link between anakinra use, uncontrolled maternal febrile disease, and fetal outcomes. These data add to the limited knowledge regarding antenatal anakinra use and support its use in pregnant women without access to effective alternative therapies that have a larger volume of reassuring safety data. References: [1] Götestam Skorpen C, et al. The EULAR points to consider for use of antirheumatic drugs before pregnancy, and during pregnancy and lactation. Ann Rheum Dis2016;75:795–810. [2] Chang Z, et al. Anakinra use during pregnancy in patients with cryopyrin-associated periodic syndromes (CAPS). Arthritis Rheumatol2014;66:3227–32. [3] Youngstein T, et al. International multi-centre study of pregnancy outcomes with interleukin-1 inhibitors. Rheumatology (Oxford). 2017;56:2102–2108. [4] Abe K, et al. Maternal febrile illnesses, medication use, and the risk of congenital renal anomalies. Birth Defects Res A Clin Mol Teratol2003;67:911–8. Disclosure of Interest: None declared